Eleições municipais 2012 e 2016 e a sub-representação feminina: a influência de fatores político-institucionais - PEREIRA, Alan da Silva (Tribunal Regional Eleitoral de Santa Catarina, 2021)
This article presents the election of women to City Councils as an object of investigation, based on evidence that women are underrepresented in legislative positions. Specifically, the research relates the difficulty of women accessing decision-making are nas based on two variables in the literature: district size and party ideology. Using a cor relation methodology, the hypothesis test in dicated that district size does not sufficiently explain why few women are elected in Brazil. The study aimed to verify the relationship between the election of women and the ide ological differences between the parties. The results did not show great variation in the election of women regarding party ideology.